Radiative transfer in moving spherical atmospheres: II. analytical solution for fully relativistic radial motions. - Baschek, Bodo; Efimov, Garij V.; Waldenfels, Wilhelm von; Wehrse, Rainer (Astronomy and astrophysics, 1997)
Based on the well known solution of the time-independent radiative transfer equation along a ray and on suitable point transformations, general quadrature solutions of the monochromatic transfer equation for plane-parallel, spherically-symmetric and arbitrarily shaped 3D configurations with differential motion are derived for the observer's and the comoving frame. The source function is assumed to be given; however, the scattering case requires only a simple iteration in addition. Since complete Lorentz transformations are used, the velocities are not restricted. It is shown that in many cases the explicit form of the transfer equation - which often is quite complicated - is not required for the determination of the specific intensities.
Gesehen am 17.04.2023